New Approach for The Turbidimetric Determination of Iron(III) in Drug Samples of Different Origins Using Homemade Linear Array Ayah 5SX1-T-1D-CFI Analyser - M.A. Shakir, Issam; K. Hammood, Mohammad (Iraqi Journal of Science, 2023)
A new Turbidimetric method characterized by simplicity, accuracy and speed for determination of iron(III) in drug samples by continuous flow injection analysis. The method was based on the formation of complex for iron(III) with 8-hydroxyquinoline in presence of ammonium acetate as a medium for the formation of deep green precipitate and this precipitate was determined using homemade Linear Array Ayah-5SX1-T-1D continuous flow injection analyser. The optimum parameters were 2.6 mL.min-1 flow rate using H2O as a carrier, 1.9 mL.min-1 (14 mmol.L-1) ammonium acetate, 2.4 mL.min-1 (14 mmol.L-1) 8-hydroxyquinoline, 60 L sample volume and open valve for the purge of the sample segment. Data treatment shows that linear range 0.1-8.0 mmol.L-1 while L.O.D 4.8×10-9 M/sample equivalent to 16.1 pg/sample from the stepwise dilution for minimum concentration of lowest concentration in linear dynamic range of the calibration graph. The correlation coefficient (r) was 0.9911 while percentage linearity (%r2) C.O.D was 98.24%. R.S.D.% for the repeatability (n=6) was <1% for determination of iron(III) with concentration 4 and 8 mmol.L-1. The method was applied successfully for the determination of iron(III) in pharmaceutical preparations. Using paired t-test between the newly developed method and official method; shows that there were no significant differences between either methods. On this basis the new method can be accepted as an alternative analytical method for determination of iron(III) in pharmaceutical samples.